Predictors of maternal and fetal outcome in severely anemic pregnant mothers: A sequential mixed methods study - V. Saraswathy; M. Subashini; R. L. Jayavani; Usha Vaithiyanathan; Reenaa Mohan; R. Sindhuri (Journal of Family Medicine and Primary Care)
Introduction: Severe anemia in pregnancy increases maternal and neonatal morbidity and mortality in the antenatal period. Objective: To find out the maternal and fetal outcomes in severely anemic pregnant women and explore the reason for the persistence of severe anemia in pregnant women. Materials and Methods: Sequential explanatory mixed method study (Quan-Qual) was conducted in the Government Women and Children Hospital for a period of 1 and half years. Most of the people were from rural backgrounds and belonging to low socioeconomic status have been registered. Quantitative data were collected from 125 severe anemic cases; a consecutive sampling technique was applied. In-depth interviews were conducted among purposively selected severe anemic patients (n = 15) who were vocal and willing to explore the reason for the persistence of anemia. The interviews were conducted till the point of saturation. Ethical principles were adhered throughout the study. Quantitative data were anlyzed using SPSS software. Manual content analysis was done for qualitative data. Results: Among 125 severe anemic patients, 12.8% patients had preterm labour, about 23.2% had inadequate lactation, and 13.6% had a puerperal febrile illness. It was found 41.6% of neonates had respiratory distress and 33.6% had the refusal of feeds. When compared to vaginal delivery, women undergoing cesarean section have 3.2 times (95% confidence interval 1.39-7.32) higher odds of developing maternal complications. Nagelkerke's R2 value for the model was 11.1%. Five broad categories namely Family centric nature, Lack of awareness, Pill burden, Food Fads, and Myths related to iron intake emerged from the study. Conclusion: Complications can occur in mothers and neonates if anemia is not corrected in early trimester.